Yasak, Serving and Zakhrebetnyye Tatars: Tyumen Uyezd of 17 Century - G. K. Samigulov (Научный диалог)
The issues of social structure of the local Turkic population of the Tyumen uyezd are considered. Attention is paid to the fact that the division of local population into serving, yasak and zakhrebetnyye Tatars occurred within the Moscow state. The analysis of published and newly discovered sources is presented. The novelty of the research is seen in the fact that the author tried to abstract from the existing concepts of formation of class groups of the Turkic population of the Tyumen uyezd, focusing on archival materials. In today’s conditions, in the presence of a large number of literature, sometimes it is useful to return to the analysis of primary sources. The study proved that the groups of yasak, serving and zakhrebetnyye Tatars separated from the local tribal associations. Serving Tatars consist mainly of representatives of the elite of these groups. Zakhrebelnyye Tatars was the name for a privileged group, consisting of close relatives of serving Tatars; its representatives were to change the serving Tatars of departures by age, illness, or death. Yasak Tatars was a layer of tax-paying population. At the same time, all three groups did not lose touch with each other. This is also confirmed by the fact that all these groups shared the right to hunting, fishing and other lands.